(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The use of flexible materials has the potential to offer a step-change reduction in the cost of wave energy devices by enabling them to absorb more extreme wave loads through their structural responses. Flexible wave energy converters are often manufactured from polymer, fabric, or reinforced polymer components. The elastic modulus, fatigue performance, seawater ageing, and manufacturing process determine the effectiveness of flexible components at replacing their rigid counterparts. During design, it is necessary to assess the hydrodynamic response of the WEC structure to different wave conditions. This work investigates the hydro-elastic response of a submerged polymer membrane, held in a horizontal frame, exposed to regular wave loading. Fast-Fourier Transform analysis enabled assessment of the non-linear response of the membrane exposed to the different wave conditions. The ratio of harmonic to measured wave amplitude ratio gives insight into the excitation mode of the membrane as a function of frequency. It is found that the peak response of the membrane tends to coincide with the fundamental frequency of regular waves. By varying the ratio of membrane length to wavelength an understanding is provided of the hydro-elastic response of the polymer membrane which should be useful in validating software used in the design of flexible WECs.